Diabetic patients treated with metformin during early stages of Alzheimer's disease show a better integral performance: data from ADNI study (2022)
We evaluated the effect of the antidiabetic drug metformin on patients enrolled in the ADNI study considering patients with mild cognitive impairment (MCI) due to Alzheimer's disease (AD). Employing data from this observational study, we performed a principal component analysis focusing on the cognitive sphere by evaluating data from neuropsychological tests included in a modified version of the Alzheimer's Disease Cooperative Study-Preclinical Alzheimer Cognitive Composite (ADCS-PACC). Second, we included the levels of amyloid-beta, tau, and phosphorylated tau in CSF. We found that MCI metformin-treated patients were globally characterized as subjects with a better cognitive performance and CSF biomarkers profile than the mean population of MCI patients. On the other hand, control subjects and type 2 diabetes patients (T2D) were paired by age, gender, ApoE allele, and years of education, defining three groups: MCI, MCI + T2D, and MCI + T2D + metformin. We evaluated the effect of T2D and metformin treatment employing the PACC score and composites defined from standardized ADNI variables to evaluate the memory and learning function. We found that MCI + T2D patients had a worse cognitive performance than MCI patients, but this deleterious effect was not observed in MCI + T2D + metformin patients. These cognitive variations were associated with changes in cortical thickness and hippocampal volume. Finally, no differences were found in metabolic plasmatic parameters (glycemia, cholesterol, triglycerides). Our study-employing different strategies for data analysis from the global study ADNI-shows a beneficial effect of metformin treatment on cognitive performance, CSF biomarkers profile, and neuroanatomical measures in MCI due to AD patients.